4a-9*2=3

Simple and best practice solution for 4a-9*2=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-9*2=3 equation:


Simplifying
4a + -9 * 2 = 3

Multiply -9 * 2
4a + -18 = 3

Reorder the terms:
-18 + 4a = 3

Solving
-18 + 4a = 3

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 4a = 3 + 18

Combine like terms: -18 + 18 = 0
0 + 4a = 3 + 18
4a = 3 + 18

Combine like terms: 3 + 18 = 21
4a = 21

Divide each side by '4'.
a = 5.25

Simplifying
a = 5.25

See similar equations:

| 9b+5(2b+3)=41 | | 4(2n-3)=5n+9 | | 9/4/2 | | -6+r=49 | | .3x-4=.1(x-10) | | 8c+2(3+c)=46 | | -20u^4-17u^2-3=0 | | -42=q-15 | | 50-2X=100-7x | | f(x-1)=13 | | 9+2a+1=3a-8 | | 4x-22=62+2x | | -z+1=2-3y-x | | 3(x-2)-4(x+4)=-2(x-6) | | -14+3(x+10)=7(2x+5)-4 | | -7(6-7b)+6=-134 | | Z-2-3y=2x | | 6x-18=5x+15 | | h-49=13.8 | | 3x-1=7-3y+2 | | 16+144t+324t^2=0 | | 3(x-20)-4(x+4)=-2(x-6) | | 4c(a-6)+7(a-6)= | | X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 | | 2x+6(1+5x)=230 | | (2x-7/4)=0 | | 25=k/5;k=5 | | x-3+2x=33 | | 8-5x=42 | | -2(3-5k)=-76 |

Equations solver categories